2022
DOI: 10.1136/sextrans-2022-055499
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of adherence to daily PrEP measured as intracellular tenofovir diphosphate concentrations over 24 months of follow-up among men who have sex with men

Abstract: ObjectivesAdherence is key to the effectiveness of oral pre-exposure prophylaxis (PrEP) to prevent HIV. Therefore, we aimed to explore factors associated with adherence to daily PrEP (dPrEP).MethodsMen who have sex with men (MSM) using dPrEP (emtricitabine/tenofovir disoproxil) within the Amsterdam PrEP demonstration project at the Public Health Service of Amsterdam, provided dried blood spots (DBS) 12 and 24 months after PrEP initiation. From DBS, we determined intracellular tenofovir diphosphate (TFV-DP) con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Furthermore, another behavior, and potential predictors of this behavior, that might be interesting to explore over time in future research among PrEP users is PrEP adherence. Previous studies in the Netherlands showed that adherence to daily and event-driven PrEP based on tenofovir diphosphate levels measured with dried blood spots was generally high (Jongen et al, 2021a , 2021b ; van den Elshout et al, 2023 ). They also found that several determinants, such as age and condomless anal sex with a casual partner, was associated with adherence, and that adherence may decrease over time (van den Elshout et al, 2023 ).…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, another behavior, and potential predictors of this behavior, that might be interesting to explore over time in future research among PrEP users is PrEP adherence. Previous studies in the Netherlands showed that adherence to daily and event-driven PrEP based on tenofovir diphosphate levels measured with dried blood spots was generally high (Jongen et al, 2021a , 2021b ; van den Elshout et al, 2023 ). They also found that several determinants, such as age and condomless anal sex with a casual partner, was associated with adherence, and that adherence may decrease over time (van den Elshout et al, 2023 ).…”
Section: Discussionmentioning
confidence: 98%
“…These levels were also well above the protective thresholds at all time points up to 4 years after PrEP initiation in the majority of participants. A subgroup of participants was included in a nested RCT assessing the effect of an app providing visualised feedback to increase adherence, as reported previously [ 24 , 36 ], which could have possibly been a contributing factor to adherence. The absence of any HIV infection after 1 year on PrEP provides further evidence that PrEP use can be sustainable and efficacious in preventing HIV over the longer course.…”
Section: Discussionmentioning
confidence: 99%
“…These levels were also well above the protective thresholds at all time points up to 4 years after PrEP initiation in the majority of participants. A subgroup of participants was included in a nested RCT assessing the effect of an app providing visualised feedback to increase adherence, as reported previously(23, 33), which could have possibly been a contributing factor to adherence. The absence of any HIV infection after one year on PrEP provides further evidence that PrEP use can be sustainable and efficacious in preventing HIV over the longer course.…”
Section: Discussionmentioning
confidence: 99%